Immagini classiche nel Seafarer e nelle culture del Nord - Cucina, Carla (Classiconorroena, 2014)
This paper is the text of a lecture held on February 6th, 2009, at the Istituto Svedese di Sudi Classici in Rome, during the annual meeting of the Società Culturale Classiconorroena. A rich selection of images and topics with symbolical or allegorical implications has long been investigated within the Anglo-Saxon poetical corpus. A recent thorough study – and new edition – of the text of The Seafarer by the Author has proved that themes like sea journeying, ship and winter cold were widely spread and accepted by scopas in a metaphorical sense, mainly as Christian symbols for man’s life, Church (or Christian faith, or soul) and sin, respectively. Germanic ethos or ideals may stand in the background, of course, and sometimes they have proved indeed decisive in giving poetry that realistic power and liveliness so peculiar to the Old English tradition. But a great part of the Anglo-Saxon poetical production – written down in steady Christian times and in a monastic milieu – shows undisputable evidence of being drawn from Christian sources, ultimately from Latin patristic literature. The works of the Fathers, in their turn, filter not only the Scripture, but also classical imagery and rethorical models; so that, in the end, all these tracks are left clean and clear-cut on the Anglo-Saxon ground as well. The aim of this paper is to investigate to what extent images like the winter cold and the sea sailing ship may act as symbols also in the medieval Scandinavian tradition, i.e. in Old Icelandic literature and on Viking Age rune stones. The Author’s first concern is about ice and cold imagery, as it results in Old English and Old Icelandic poetry, down to the Swedish Renaissance tradition of Olaus Magnus’ Historia de gentibus septentrionalibus and drawing for comparison back to the poetical stock of Latin literature possibly known to litterate men in medieval England and Iceland (see § 2). Recurrent ideas and phrases result common to both Latin and Germanic authors, for instance regarding winter cold binding or closing the ground, or ice building ‘bridges’ (that is, allowing to walk where usually river or sea waters run or flow). Great similarities occur in the treatment and phrasing of these stock images, so that bonds of cold and bridges of ice, but also some other hints of severe cold, such as hairs and beard frozen into icicles, are frequently met in natural descriptions of Scythia (by Latin poets) and Northern Europe (by Scandinavian and Anglo-Saxon authors), being at the same time a signal of deep psycological discomfort and misery. Old Scandinavian reception of the rich symbolical Christian tradition concerning the ship and sea journeying is the second point of the present article (§ 3). First of all (§ 3.1), the ship appears on some Viking Age rune stones, which prove to be especially significant in Christian allegorical terms, since they show the shape of a ship surmounted by a great ornamental cross. These Swedish monuments form a typologically homogeneous group, in which the design and pattern model – with no realistic hint of mast and sail behind the richly decorated cross – certainly points to a symbolical meaning. The Author maintains that this metaphorical ‘crusade’ ship is taken as a figure of the Church: on board, the faithful is granted a safe passage to everlasting bliss, being this boat the only secure place in the dangerous sea of life in this world. In a more specific sense, this ship may be considered Christ himself as our Saviour on the cross; the easy visual proximity of the mast crossed by the yard and the Cross itself helps Christian authors and artists to elaborate upon this image as one of the most powerful allegories in the Christian doctrine. At last (§ 3.2), two very interesting examples of Old Icelandic ship allegories, which have hardly been considered by scholars, are briefly discussed. They occurr in the second booklet of the so-called ‘Physiologus manuscript’ (AM 673 a II, 4°, fols. 8r-9r), which is one of the oldest Icelandic manuscripts. Both ship allegories start as nautical catalogues, where parts of the ship are compared with Christian doctrinal elements or general topics, and with liturgical and monastic canon.